Use of nasal mucosal autonomic nerve response in efficacy evaluation of vidian neurectomy for allergic rhinitis: a prospective study - Liu, Linzheng; Ma, Na; Niu, Yan; Peng, Yuping; Li, Yan; Shen, Jiangjiang; He, Jiameng; Sun, Jindi (Frontiers in Neuroscience, 2025)
ObjectiveTo evaluate the use of nasal mucosal autonomic nerve responses as an objective indicator for assessing the efficacy of vidian neurectomy (VN) in treating allergic rhinitis (AR).MethodsThirty-five patients with moderate to severe AR and 35 healthy controls were included. Autonomic nerve responses were measured before and 1 month after VN surgery, using respiratory stimulation on the nasal mucosa and the opisthenar area. Three waveform types (P-type, N-type and M-type) were identified.ResultsWhile three waveform types were identified in the nasal mucosa, only the M-type was observed in the opisthenar sympathetic skin response. Preoperative measurements showed higher autonomic responses in patients with AR compared with controls. Following VN, the responses in patients with AR decreased significantly, aligning closely with the control group. No significant changes were observed in the opisthenar responses, indicating a localised effect of VN. Comorbidities such as nasal polyps, sinusitis and deviated septum did not impact the results.ConclusionNasal mucosal autonomic nerve response provides a reliable, objective measure for evaluating the effectiveness of VN in treating AR.